What is the main mechanism of the origin of phosphorylation sites? Still an open question. Issue 3 (28th March 2017) - Wang, Yu‐Yu; Su, Zhi‐Xi; Gu, Xun
Abstract: In spite of high‐throughput phosphoproteomics for protein kinase–phosphorylation site interactions, the evolutionary mechanism for the origin of protein phosphorylation remains a mystery. Pearlman and his colleagues proposed that some phosphorylation sites may have evolved from acidic amino acids, because those negatively charged amino acids (Asp/Glu) can mimic the phosphorylated state of a protein. Moreover, phosphorylation has the potential to conditionally restore the salt bridge that was originally constitutively formed by Asp/Glu. Although this insightful mimic hypothesis has been supported by several examples, we point out that the replacements from Asp/Glu to serine/threonine require at least two non‐synonymous nucleotide substitutions, casting some doubt about whether it is the major mechanism for the origin of phosphorylation. As the intermediate amino acid types, such as Ala/Asn/Gly, are not observed frequently, we have to invoke the hypothesis of double‐mutation driven by natural selection; that is, the very strong positive selection for the second mutation has overcome the deleterious effect caused by the first mutation. Furthermore, we propose an alternative evolutionary scenario that phosphorylation was primarily evolved to introduce negative charges to the protein surface, thus reducing spurious protein–protein interactions in vivo by electrostatic repulsion. The specific protein–protein interaction could be regulated when corresponding signals change surface charges by means of dephosphorylation and other recognition mechanisms. Probably this is a more universal mechanism that provided the first step toward the emergence of more accurate cell signaling and regulation. Further study is needed to distinguish between these hypotheses.